Intellectual development in Noonan syndrome: a longitudinal study - Roelofs, Renée L. (Brain Behav, 2016)
INTRODUCTION: Although cognitive impairments in adults with Noonan syndrome seem to be limited to a low‐average intelligence and slower processing speed, studies in children with Noonan syndrome have demonstrated more extensive cognitive problems. These include deficits in language skills, memory, attention, and executive functioning. This longitudinal study is the first to investigate intellectual development in a group of individuals with Noonan syndrome. METHODS: Sixteen patients with Noonan syndrome underwent intelligence assessment both in childhood and in adulthood, using Wechsler's intelligence scales. IQ scores and Wechsler standard scores achieved in childhood and adulthood were compared. Subsequently, verbal and performance IQ in childhood were used as predictors for adult IQ and index scores. RESULTS: Compared with childhood scores, adult full‐scale IQ and performance IQ significantly increased. Adult performance IQ was higher than verbal IQ. Childhood performance IQ and verbal IQ together predicted all adult IQ and index scores, except for the processing speed index. DISCUSSION: Childhood IQ was a significant predictor of adult intelligence in patients with Noonan syndrome. Performance IQ advanced to a normal level in adulthood, while verbal IQ did not develop proportionately, resulting in a discrepancy between adult performance IQ and verbal IQ. This finding could suggest a delay in the development of executive functioning in patients with Noonan syndrome, which seems to be outgrown in adulthood.